Investigations into dry‐sliding wear behaviour of a novel composite (aluminium‐magnesium‐silicon‐copper‐silicon carbide) produced by powder metallurgy route. Issue 3 (8th March 2021) - Behera, R.K.; Samal, B.P.; Panigrahi, S.C.
Abstract: Metal‐matrix aluminium composites are satisfactory successor not only for steels, but also for aluminium‐alloys in several automotive units and components. There are various paths to get light‐weight materials with‐out compromising their toughness, strength and safety demands. Tests on dry‐sliding or un‐lubricated pin‐on‐disc tests can be performed to obtain the wear‐characteristics of metal‐matrix composites built on aluminum. In the present study, we studied the behavior of wear resistance during sliding of metal matrix aluminium composites (AMMC) at sliding speeds of 1.5 m/s and loads of 20 N and 40 N in a normal environment, and experiments have been conducted using pin‐on‐disk tribometer (Make: DUCOM tribometer). The composites were manufactured by powder treatment and presented a number of problems, such as defective bonds and inter‐facial product reactions, which alter the tribological and mechanical properties. The results have shown that wear‐rates of the prepared composites are much lesser than those of matrix‐alloy and decreased further with increasing silicon carbide content. As the normal loads increases, the cracks and combination of abrasions, delimitation and wear of the adhesives of silicon carbide particles were observed. The composite samples were studied using a scanning electron microscope before and after the wear tests and systematically analysed. Abstract : In this paper, the dry‐sliding wear behavior of a novel composite aluminum‐magnesium‐silicon‐copper‐silicon carbide (AMMC) was produced by powder metallurgy route. The newly found composite was predicted its light‐weight and high‐performance of aluminum metal matrix composites with higher Vickers hardness and lesser wear rates. Translation abstract: Metallmatrix‐Aluminium‐Verbundwerkstoffe sind nicht nur für Stähle, sondern auch für Aluminiumlegierungen in mehreren Automobileinheiten und ‐komponenten ein zufriedenstellender Nachfolger. Es gibt verschiedene Wege, um leichte Werkstoffe zu erzeugen, ohne ihre Anforderungen an Zähigkeit, Festigkeit und Sicherheit zu beeinträchtigen. Tests an trockengleitenden oder nicht geschmierten Pin‐on‐Disc‐Tests können durchgeführt werden, um die Abriebeigenschaften von Metallmatrix‐Verbundwerkstoffen auf Aluminiumbasis zu erhalten. In der vorliegenden Studie wurde das Verhalten der Verschleißfestigkeit beim Gleiten von Metallmatrix‐Aluminium‐Verbundwerkstoffen (MMC) bei Gleitgeschwindigkeiten von 1, 5 m/s und Belastungen von 20 N und 40 N in einer normalen Umgebung untersucht. Experimente wurden mit Pin‐on‐Disk Tribometer (Marke: DUCOM Tribometer) durchgeführt. Die Verbundstoffe wurden durch Sintern hergestellt und zeigten eine Reihe von Problemen, wie z. B. fehlerhafte Bindungen und Reaktionen zwischen den Grenzflächen der Partikel, die die tribologischen und mechanischen Eigenschaften verändern. Die Ergebnisse haben gezeigt, dass die Verschleißraten der hergestellten Verbundwerkstoffe viel geringer sind als die der Matrixlegierung und mit zunehmendem Siliciumkarbidgehalt weiter abnehmen. Mit zunehmender normaler Belastung wurden Risse und Kombinationen von Abrieb, Abgrenzung und Verschleiß der Klebstoffe von Siliciumkarbidpartikeln beobachtet. Die Verbundwerkstoffproben wurden vor und nach den Verschleißtests mit einem Rasterelektronenmikroskop untersucht und systematisch analysiert.